2016
DOI: 10.1080/19476337.2016.1230151
|View full text |Cite
|
Sign up to set email alerts
|

Pressurized hot water extraction and chemometric fingerprinting of flavonoids from Bidens pilosa by UPLC-tandem mass spectrometry

Abstract: The need for greener extraction procedures that are quick and efficient has prompted the evolution of pressurized hot water extraction (PHWE). Here, the extraction of flavonoids from Bidens pilosa was demonstrated using PHWE at 50°C, 100°C and 150°C. The extracts were analyzed on UPLC-qTOF-MS/ MS and 28 flavonoids of different classes were identified. Further analysis of the data using principal component analysis revealed differential distribution patterns of the identified molecules. In overall, the extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Quercetin has been reported as a crucial dietary flavonoid that is associated with plethora properties capable of suppressing certain ailments linked to chronic diseases [ 21 ]. According to Gbashi et al [ 46 ], this flavonoid aglycone has been suggested as a hepatoprotective agent. Quercetin rutinoside (molecule 7 ) with a precursor ion at m/z 609 [M-H] − was identified in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quercetin has been reported as a crucial dietary flavonoid that is associated with plethora properties capable of suppressing certain ailments linked to chronic diseases [ 21 ]. According to Gbashi et al [ 46 ], this flavonoid aglycone has been suggested as a hepatoprotective agent. Quercetin rutinoside (molecule 7 ) with a precursor ion at m/z 609 [M-H] − was identified in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that kaempferol is of great significance in managing cancer-associated ailments [ 21 , 47 ] as well as inhibiting oxidative stress [ 46 ]. Molecule 10 was identified as kaempferol rutinoside, with a precursor ion at m/z 593.1496 [M-H] − [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One or more solutes contained in a feed solution are transferred to another immiscible solvent, often by rigorously mixing the two immiscible phases, then allowing the two phases to separate [74,75]. The enriched solvent is called the extract [76]. Common solvents used for solvent extraction include methanol, acetonitrile, chloroform, ethyl acetate, isooctane, ethanol and dichloromethane [4,73,77].…”
Section: Conventional Extraction Methods For Aflatoxins In Food and Feedmentioning
confidence: 99%
“…Cosolvents are secondary solvents (usually organic solvents) that are added to subcritical water to enhance its solvation power [95,110]. The incorporation of methanol during SWE was observed to significantly (p < 0.05) increase yield of flavonoids and di-acylated cinnamic acids from Bidens pilosa [95,111]. Solvent modifiers such as salts and other reagents can alter important physicochemical properties of water such as polarity, surface tension, and hydrogen bonding strength, which results in an enhanced extractability [13,112].…”
Section: Cosolvents and Modifiersmentioning
confidence: 99%